Utopia and Ucrony: Galicia Triumphant in Nordeste (2016) by Daniel Asorey - Gaspar Jorge, Thayane (Madrygal. Revista de Estudios Gallegos, 2023)
Miguel-Anxo Murado in the essay Outra idea de Galicia (2016) contests the myth of land without history used to explain the lack of the importance of Galician history in Europe. Murado attributes the problem to historians and to the priorities of those who, when writing the history of Spain, relegate most Galician episodes to oblivion. In line with this analysis and drawing on Walter Benjamin's (1996) thesis, the novel Nordeste (2016) by Daniel Asorey uses utopia and uchrony to promote a historic reparation to Galician land. In this novel, the author brushes the history against the grain and, also, changes the historical trajectory of Galicia by creating a fictional plot that intends to answer the question: “What would have happened to Galicia and to the world if the Galicians had been successful in the Guerra Irmandiña?”. Murado, in his essay, reach the conclusion that history and power are synonymous and that power is restored by Daniel Asorey when he defined the utopian, colonizing and imperialist Galicia, holder of colonies in Brazil. Nordeste is a work that seeks to give back the silenced voice of the subaltern and submissive, the losers in historical narratives, according to Benjaminian thought. This book manipulates history and time through the connection of four female characters: Maria Bonita, the queen of the Brazilian cangaço movement; Carme de Candigas, a fictitious character and Matilda, the Galician immigrated in São Paulo, a character inspired by the American photographer, Mathilda Anderson. The fourth woman is the female representation of Galicia, the main of the imperialist and misoxin reply to the nationalist attempts of the Celtic Atlantic nations, asleep and oppresseed by imperialism and British and Spanish centralism.
Keywords: History; Uchronia; Gender Roles; Galicia; Brazil